Research of dissipative properties of alloys on the basis of iron with a nanostructural covering - Өтепов, Е.Б.; Баст, Ю.; Беркинбаева, А.С.; Мадижанова, А.Т.; Нұрғалиев, А.Қ. (Recent Contributions to Physics, 2016)
The main idea of work consists in physical modeling of process of impact during the work of a stamp and development of alloys with the increased damping properties, with a nanostructural covering. Melted steel original, legirovanny chromium (0.10-0.42%), calcium (0.16 -0.28)%, lantanom (0.18 -0.24)%. Studied the acoustic properties (sound pressure levels when the collision), internal friction, specific electric resistance of steels. Used the technique of KazNTU named after K.I. Satpayev sound emission assessment; and Tula Technological University (internal friction). Experiments have shown that melted alloys authors (BA-2, BA -3) have lower zvukoizlučeniem and high internal friction, so they are recommended for application in production.